Diffuse lung involvement in rheumatoid arthritis: a respiratory physician's perspective. Issue 3 (5th February 2023) - Huang, Hui; Chen, Ruxuan; Shao, Chi; Xu, Zuojun; Wolters, Paul J.
Abstract : Abstract: The lungs are one of the most common extra-articular organs involved in rheumatoid arthritis (RA), which is reported to occur in up to 60% to 80% of RA patients. Respiratory complications are the second leading cause of death due to RA. Although there is a wide spectrum of RA-associated respiratory diseases, interstitial lung disease is the most common manifestation and it impacts the prognosis of RA. There has been progress in understanding the management and progression of rheumatoid arthritis-associated interstitial lung disease (RA-ILD) and RA-associated respiratory diseases recently, for example, opportunistic pulmonary infectious diseases and toxicity from RA therapies. From a chest physicians' perspective, we will update the diagnosis and treatment of RA-associated ILD, methotrexate-associated lung disease, and the complication of Pneumocystis jiroveci pneumonia in RA in this review.